Purines and pyrimidines: Metabolism, function and potential as therapeutic options in neurodegenerative diseases - Kundu D.; Dubey V.K. (My University, 2025)
Various neurodegenerative disorders have various molecular origins but some common molecular mechanisms. In the current scenario, there are very few treatment regimens present for advanced neurodegenerative diseases. In this context, there is an urgent need for alternate options in the form of natural compounds with an ameliorating effect on patients. There have been individual scattered experiments trying to identify potential values of various intracellular metabolites. Purines and Pyrimidines, which are vital molecules governing various aspects of cellular biochemical reactions, have been long sought as crucial candidates for the same, but there are still many questions that go unanswered. Some critical functions of these molecules associated with neuromodulation activities have been identified. They are also known to play a role in foetal neurodevelopment, but there is a lacuna in understanding their mechanisms. In this review, we have tried to assemble and identify the importance of purines and pyrimidines, connecting them with the prevalence of neurodegenerative diseases. The leading cause of this class of diseases is protein misfolding and the formation of amyloids. A direct correlation between loss of balance in cellular homeostasis and amyloidosis is yet an unexplored area. This review aims at bringing the current literature available under one umbrella serving as a foundation for further extensive research in this field of drug development in neurodegenerative diseases. © 2021 Bentham Science Publishers.